PENGARUH KONTEN MARKETING DAN ULASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION DI PLATFORM TIKTOK PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI SEMESTER VIII - Riska Amelia Febriyanti; Maria Agatha Sri Widyanti Hastuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The rapid growth of social media platforms, particularly TikTok, has significantly transformed consumer purchasing behavior in the digital marketplace. Engaging marketing content and product reviews have emerged as influential information sources that shape consumers’ purchasing decisions, especially in the fashion industry. This study aimed to examine the effects of content marketing and product reviews on purchase decisions for fashion products on TikTok among students of the Economic Education Study Program at Universitas Bhinneka PGRI. A quantitative research approach was employed using a survey method. The study involved 73 respondents selected through simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The findings revealed that content marketing had a positive and significant effect on purchase decisions (t = 3.355, p = 0.001). Similarly, product reviews demonstrated a positive and significant influence on purchase decisions (t = 4.007, p = 0.000). Furthermore, content marketing and product reviews simultaneously exerted a significant effect on purchase decisions for fashion products on TikTok (F = 265.368, p = 0.000). The Adjusted R Square value of 0.880 indicates that 88% of the variation in purchase decisions can be explained by content marketing and product reviews, while the remaining 12% is attributed to other factors beyond the scope of this study. These findings highlight the critical role of high-quality marketing content and credible product reviews in influencing consumer purchase decisions within video-based social commerce platforms. ABSTRAK Perkembangan media sosial TikTok telah mengubah pola konsumsi masyarakat, khususnya dalam pembelian produk fashion secara daring. Konten pemasaran yang menarik dan ulasan produk yang tersedia pada platform digital menjadi sumber informasi penting yang memengaruhi keputusan konsumen. Penelitian ini bertujuan menganalisis pengaruh konten marketing dan ulasan produk terhadap keputusan pembelian produk fashion di TikTok pada mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI. Penelitian menggunakan pendekatan kuantitatif dengan metode survei. Sampel penelitian berjumlah 73 mahasiswa yang dipilih melalui teknik simple random sampling. Data dikumpulkan menggunakan kuesioner dan dianalisis dengan regresi linear berganda. Hasil penelitian menunjukkan bahwa konten marketing berpengaruh positif dan signifikan terhadap keputusan pembelian (t = 3,355; p = 0,001). Ulasan produk juga berpengaruh positif dan signifikan terhadap keputusan pembelian (t = 4,007; p = 0,000). Secara simultan, konten marketing dan ulasan produk berpengaruh signifikan terhadap keputusan pembelian produk fashion di TikTok (F = 265,368; p = 0,000). Nilai Adjusted R Square sebesar 0,880 menunjukkan bahwa 88% variasi keputusan pembelian dapat dijelaskan oleh kedua variabel tersebut, sedangkan 12% sisanya dipengaruhi oleh faktor lain di luar model penelitian. Temuan ini mengindikasikan bahwa kualitas konten pemasaran dan ulasan produk menjadi faktor penting dalam membentuk keputusan pembelian konsumen pada platform social commerce berbasis video pendek.